2007
DOI: 10.1590/s1415-47572007000300018
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability analysis for grain filling duration and yield traits in spring wheat (Triticum aestivum L. em. Thell.)

Abstract: A diallel analysis of wheat (Triticum aestivum L. em. Thell) parents (n = 11) and their F 1 (n = 55) and F 2 (n = 55) offspring was carried out for the following four traits: grain filling duration (GFD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
11
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 24 publications
5
11
0
4
Order By: Relevance
“…The magnitude of sca variance was greater than gca variance for all the traits ( Table 3). The obtained results are in accordance with the findings of Kashif and Khaliq (2003), Kamaluddin et al, (2007) but are in contrary with the findings of Akram et al, (2011) and Khan et al, (2007) who have reported the predominance of gca variance for the trait yield per plant. Further, the ratio of GCA to SCA variance was less than unity which indicated the preponderance of nonadditive gene action in controlling these traits.…”
Section: Resultssupporting
confidence: 78%
“…The magnitude of sca variance was greater than gca variance for all the traits ( Table 3). The obtained results are in accordance with the findings of Kashif and Khaliq (2003), Kamaluddin et al, (2007) but are in contrary with the findings of Akram et al, (2011) and Khan et al, (2007) who have reported the predominance of gca variance for the trait yield per plant. Further, the ratio of GCA to SCA variance was less than unity which indicated the preponderance of nonadditive gene action in controlling these traits.…”
Section: Resultssupporting
confidence: 78%
“…Efeitos gênicos aditivos e não aditivos, no controle da expressão da produção de grãos em trigo, foram verificados na geração F 1 , por Kamaluddin et al (2007), e nas gerações F 1 e F 2 por Joshi et al (2004). Zeeshan et al (2013) constataram, por meio de análise dialélica, contribuição de efeitos gênicos não aditivos na geração F 1 superior a dos efeitos aditivos, para produção de grãos e seus componentes.…”
Section: Resultsunclassified
“…Yan and Hunt (2002) evaluated the GCA of parents and the SCA of the crosses via a diallel design under multiple environments. The higher contribution of GCA effects has been linked to the additive effects that controlled expression of the traits in wheat (Kamaluddin et al, 2007). Kumar et al (2011) identified the best specific and general combiners that were efficient for breeding days to flowering and grain yield per plant in seven bread wheat cultivars.…”
mentioning
confidence: 99%